Research on Relation Between Distortion of Carburizing and Quenching Gears and Grinding Amount of Gear Flanks - Zhao Shaofu; Xu Hongxiang; Chen Shengchao; Wang Hongwei; Zhang Heng; Rong Zeyu; Wang Jun; Cao Xinmin (Jixie chuandong)
There are many kinds of distortion of carburizing and quenching gears, but they will be reflected in the grinding amount of gear flanks. Through theoretical analysis and long-term production practice, it is found that the change of tip diameter has the greatest influence on the grinding amount, the change of the helix angle and the circumferential warpage of gear rims takes the second place, and other factors have relatively little influence. The empirical formulas for calculating the maximum and minimum grinding amount of the tooth flank are given, according to the change of the tip diameter and other parameters. These formulas can be used to determine the case-hardened depth (CHD) in drawings, the reserved grinding amount of gear flanks during gear hobbing, and the target CHD during carburizing and quenching. After carburizing and quenching, the maximum and minimum grinding amount and the actual CHD can be calculated and predicted according to these formulas, so as to provide guidance for subsequent production.